Instruction au sein de la famille versus instruction au sein de l'école - Carlos Roberto Jamil Cury (Les éditions de la Maison des sciences de l'Homme, 2009)
The compulsory attendance at school takes its origine in the principle of compulsory education stated in the Brazilian Law - obligation which is also present in the Federal Constitution. The National Council of Education has seen this principle contested by the social movement known as Home schooling, first developed in the USA, which now exists in Brazil too. This article aims to present the general components of this controversy, such as the historical aspects and the main arguments used by both sides. The law and its official interpretation make explicit the State's duty about the mandatory enrolment at schools.